High basal metabolic rate/fat-free mass ratio in Japanese elite male athletes can be attributed to body composition - Tatsuta, W.; Yokota, Y.; Kamei, A.; Tawara, N.; Kawahara, T.; Taguchi, M.; Higuchi, M. (Japanese Journal of Physical Fitness and Sports Medicine, 2012)
The aim of the present study was to evaluate the relation between basal metabolic rate (BMR) and body composition in 29 Japanese elite male athletes (age 25.6±3.7y, height 175.6±7.0cm, body weight 74.7±12.8kg, fat-free mass (FFM) 64.9±9.3kg). The subjects were classified into three groups according to their FFM. There was a significant difference in BMR/FFM between S-group (less than 0.5SD of average FFM) and L-group (more than 0.5SD). The parcentage of RM to body weight in S-group was significantly higher than in L-group. In conclusion, high basal metabolic rate/fat-free mass ratio in Japanese elite male athletes can be attributed to body composition.